Entrepreneurship Management Strategies in Enhancing the Competitiveness of MSMEs in the Digital Economy Era - Rahaded, Lucia Klamensia (Economics and Digital Business Review, 2025)
Digital transformation has created new opportunities and challenges for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. In this context, entrepreneurship management strategies have become a crucial element in ensuring the sustainability and competitiveness of MSMEs amid rapid technological changes. This study aims to identify and analyse the entrepreneurship management strategies used by MSMEs in facing the digital economy era. Using a qualitative approach with case studies on several MSMEs in the trade and service sectors, data were collected through in-depth interviews and participatory observation. The results of the study indicate that a combination of product innovation, the use of digital technology (such as e-commerce and social media), and managerial capacity development are key factors in strengthening the competitive position of MSMEs. Additionally, adaptability to market changes and the ability to build digital business networks were also found to significantly contribute to business growth. The implications of these findings highlight the need for policy support and continuous training to enhance digital literacy and strategic management among SMEs.